Meaningful Work and the Voices of Others in Frontline Occupations - Humle, Didde Maria; Frandsen, Sanne (Nordic Journal of Working Life Studies, 2026)
This article explores meaningful work across two frontline occupations, bank advisors and schoolteachers. We build on narrative research focusing on the role of stories and storytelling in the sensemaking and identity construction processes related to work to explore the importance of others in the perception and construction of everyday work as meaningful. To study this, we examine the narrative construction of meaningful work in everyday work stories of self, work, others, and organizations as (ante)narrative identity construction processes. Our analysis shows that ‘making a difference by helping others’ is the predominant theme when sharing stories of everyday work situations perceived and constructed as meaningful. Three contributions are made. First, the narrative construction of meaningful work is collective and dynamic; second, others have a powerful voice in negotiating the meaningfulness of work; and third, negative public attention affects the possibility of assessing work as meaningful.